Character, Conformity, or the Bottom Line? How and Why Downsizing Affected Corporate Reputation - Love, E. Geoffrey; Kraatz, Matthew (Academy of Management Journal, 2009)
The aim of this study is to illuminate reputational change processes and identify the underlying theoretical mechanisms. We draw upon extant literature to develop three distinct explanations for reputational change, respectively emphasizing criteria of organizational “character,” symbolic conformity, and technical efficacy. We evaluate these explanations by examining the reputational consequences of corporate downsizing. Our results show that downsizing exerted a strong, negative effect on reputation, consistently with the character explanation. However, significant moderation of this negative effect by other factors, including stock market reaction and downsizing's overall prevalence, indicates the need for a multitheoretical approach to reputational change.